2012
DOI: 10.1371/journal.pone.0050473
|View full text |Cite
|
Sign up to set email alerts
|

Unique Substrates Secreted by the Type VI Secretion System of Francisella tularensis during Intramacrophage Infection

Abstract: Gram-negative bacteria have evolved sophisticated secretion machineries specialized for the secretion of macromolecules important for their life cycles. The Type VI secretion system (T6SS) is the most widely spread bacterial secretion machinery and is encoded by large, variable gene clusters, often found to be essential for virulence. The latter is true for the atypical T6SS encoded by the Francisella pathogenicity island (FPI) of the highly pathogenic, intracellular bacterium Francisella tularensis. We here u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(109 citation statements)
references
References 62 publications
(101 reference statements)
2
104
1
2
Order By: Relevance
“…The presence of an N-terminal signal sequence and our combined biochemical and genetic data suggesting that IglE is an outer membrane-anchored lipoprotein are inconsistent with the results of a second study which showed that IglE coupled to a beta-lactamase reporter is secreted from the cell in a manner that is dependent on other core FPI proteins (37). The same authors also noted that PdpE (a second secreted FPI-encoded protein) also possesses a signal peptide (37).…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The presence of an N-terminal signal sequence and our combined biochemical and genetic data suggesting that IglE is an outer membrane-anchored lipoprotein are inconsistent with the results of a second study which showed that IglE coupled to a beta-lactamase reporter is secreted from the cell in a manner that is dependent on other core FPI proteins (37). The same authors also noted that PdpE (a second secreted FPI-encoded protein) also possesses a signal peptide (37).…”
Section: Discussioncontrasting
confidence: 92%
“…The same authors also noted that PdpE (a second secreted FPI-encoded protein) also possesses a signal peptide (37). This raises the intriguing possibility either that the Sec and T6SS pathways are connected in Francisella or that some FPI-secreted substrates (i.e., IglE) have two biological functions, one which requires a membrane-anchoring lipid moiety (e.g., T6SS assembly) and another where soluble protein is required (e.g., as a T6SS substrate of unknown function).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Most likely these features are not modulated directly by IglC but result from the lack of a functional T6SS due to the essential role of the protein for the secretion system. It should be noted, however, that no defined role of IglC for the secretion machinery has been demonstrated, and in fact, a recent publication demonstrated that it is secreted during macrophage infection (46).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms allowing F. tularensis to reach and multiply within the eukaryotic cell cytosol are increasingly well understood. The Type 6 secretion system effectors could be new targets to inhibit intracellular growth of this pathogen [25]. Enhancing the host response to F. tularensis infection may be more hazardous because of the potential deleterious effects of inflammation.…”
Section: F Tularensis As a Bioterrorism Agentmentioning
confidence: 99%